Control of a magnetic levitation system with communication imperfections: A model-based coupling approach - Stettinger, Georg; Benedikt, Martin; Horn, Martin; Zehetner, Josef; Giebenhain, Clenn (Control engineering practice, 2017)
This work presents a control strategy to control a magnetic levitation system under the influence of coupling imperfections (disturbances). To overcome problems arising whenever the interconnections between plant and controller have a non-negligible influence on the control-loop behavior a so-called model-based coupling approach is used. The main idea of this coupling approach is to use prediction schemes based on recursively identified plant and controller models which compensate for performance degradation due to coupling imperfections. Coupling failures such as time-delays, data-losses and noise drastically influence the control-loop performance. Especially when systems in form of real hardware (real-time systems) are present such disturbances have to be handled adequately. To demonstrate the effectiveness of the model-based coupling approach, a control-loop of a magnetic levitation system is analyzed in simulation as well as in real world laboratory setup (HiL simulation). Furthermore a first insight into the stability analysis of closed-loop systems including the model-based coupling technique is performed for a simplified configuration. •Model-based compensation of coupling imperfection effects.•Fault Tolerant Control of a magnetic levitation system.•The designed coupling strategy is verified by simulations and experiments (HiL simulations).